2019
DOI: 10.1108/ijm-04-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Women on boards and CEO pay-performance link

Abstract: Purpose The purpose of this paper is to investigate the crucial question of whether gender diversity in boardroom is associated with CEO pay and CEO pay-performance link. Design/methodology/approach The authors used the data of companies listed on the Pakistan Stock Exchange for a sample consisting of KSE-100 index companies for the period of five years. The authors used the ordinary least square regression technique to test the developed hypotheses. The authors also used the two-step Heckman selection model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 73 publications
(148 reference statements)
3
24
0
2
Order By: Relevance
“…Self-selection bias may be another possible issue in the validity of our least squares outcomes. This posits that heterogeneous boards and non-heterogeneous boards have different characteristics, and that it is possible that, due to these characteristics, firms pay a higher dividend, instead of female directors' presence on the board (Usman et al, 2019). To resolve this problem, we followed the literature (Chen et al, 2017;Faccio et al, 2016;Liu, 2018) and employed PSM.…”
Section: Propensity Score Matching (Psm)mentioning
confidence: 99%
“…Self-selection bias may be another possible issue in the validity of our least squares outcomes. This posits that heterogeneous boards and non-heterogeneous boards have different characteristics, and that it is possible that, due to these characteristics, firms pay a higher dividend, instead of female directors' presence on the board (Usman et al, 2019). To resolve this problem, we followed the literature (Chen et al, 2017;Faccio et al, 2016;Liu, 2018) and employed PSM.…”
Section: Propensity Score Matching (Psm)mentioning
confidence: 99%
“…These prescriptive reforms and regulations are driven by theoretical and empirical evidence, which suggests that female leadership in top management enhances the quality of the decision-making process. For instance, empirical studies have shown that the presence of women in top management is associated with higher auditing quality (Aldamen et al , 2018; Lai et al , 2017; Harjoto et al , 2015; Huang et al , 2014), less financial misreporting (Gupta et al , 2020; Garcia-Sanchez et al , 2017; Liu et al , 2016), better corporate performance (Terjesen et al , 2016; Post and Byron, 2015), higher monitoring intensity (Zalata et al , 2019; Gull et al , 2018; Usman et al , 2018; 2019a, 2021), lower cost of debt (Usman et al , 2019b, 2019c) lower audit fee (Alkebsee et al , 2021) and fewer acquisitions (Chen et al , 2016; Huang and Kisgen, 2013). Despite the positive impact of female leadership on firm outcomes, the consideration of female CEO aspirants in succession planning remains low.…”
Section: Introductionmentioning
confidence: 99%
“…A core idea of upper echelon theory is that directors differ cognitively, which then influences company behaviors and outcomes (Hambrick, 2007; Hambrick and Mason, 1984). Some cognitive differences may be rooted on gender, and researchers have recognized that the gender diversity on board of directors (BODs) greatly influences corporate behavior (Usman et al. , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A core idea of upper echelon theory is that directors differ cognitively, which then influences company behaviors and outcomes (Hambrick, 2007;Hambrick and Mason, 1984). Some cognitive differences may be rooted on gender, and researchers have recognized that the gender diversity on board of directors (BODs) greatly influences corporate behavior (Usman et al, 2019). For example, the previous studies found that women tend to be more sensitive, more compassionate and more cautious than men, which have more likely led to more ethics-oriented and discreet behavior (Gilligan, 1982).…”
Section: Introductionmentioning
confidence: 99%